PROSEDUR AUDIT KAS DAN SETARA KAS PADA PT. DEF OLEH KAP BHARATA, ARIFIN, MUMAJAD, DAN SAYUTI - Rifa Khoffifah (2021)
The Bharata, Arifin, Mumajad, and Sayuti Public Accounting Firm (KAP BAMS) is a KAP that has received permission from the Minister of Finance and is registered with the Financial Services Authority (OJK) whose services are in the field of general auditing such as auditing financial statements against one of BAMS' KAP clients. namely PT. DEF which is engaged in employment services. Cash and cash equivalents being one of the other assets that are liquid assets and almost every company's transactions with cash and cash equivalents, they can have the potential for fraud and are important. So there is a need for an examination of cash and its equivalents to assess the fairness of what has been presented in the financial statements by an independent and competent auditor. This report aims to determine the audit procedures for cash and cash equivalents at PT. DEF by KAP BAMS. Results Based on the audit shows that all cash and cash equivalents have been recorded fairly in all material respects.